Sammy the Sea - Hoff, Dyd; Nang ChanYeema (New York, USA HarperCollins Publisher, Inc., 1959)
Anxious to see what life is outside the zoo, Sammy the seal explores the city, goes to school, and plays with the children but decides that there really is no place like home.
Keywords: Juvenile Fiction